TINJAUAN HUKUM TERHADAP PIHAK YANG BERITIKAD BURUK DALAM ASURANSI - HARDYLES MDKH (University of North Sumatera, 2013)
Abstract : In meeting the needs of human life is always faced with the possibility of the occurrence of events is uncertain, the uncertain situation may exist in various forms and events that are usually always want to avoid, and commonly known risks. One man attempts to shift the risk itself is entered into an agreement with the devolution or transfer of risk to another party. Sharing of risk was done by a policy on the insurance company. But in practice the claims payment process is not as easy as it seems, this is because a lot of processes to go through before a claim will be paid, not even melted because of many things and one of the things that most often the problem is due to the prospective insured to peruse the contents of the contract of insurance to be entered. It should society must understand the clauses contained in the policy and the insurance company was already supposed to explain in detail the agreements contained in the policy so as not to cause disagreement in response to the content rather than the insurance polic and insurance issues are based on bad faith can be avoided. Although the disputes in the insurance sometimes can not be avoided should the parties to remain calm in the face and prefer to resolve their disputes out of court so as to achieve the concept of win-win solution for both parties. Kata Kunci : Perjanjian Asuransi, Permasalahan Asuransi, Itikad Buruk